About the Code: General Theoretical Aspect - Vladimir Valentinovich Kozhevnikov (Polit Journal Scientific Journal of Politics, 2021)
The article discusses a number of problems related to such a normative legal act as a code: its concept, increasing the proportion, correlation with other laws. Particular attention is paid to the situation according to which the code is a "product" not only of the codification of regulations, as is customary in the legal literature, but also of consolidation.